Spotlight on festival travellers: Profiles, Motivations, and Experiences of Dieng Culture Festival Travellers, Indonesia - Fajriaty Muchlis, Nur Farah; Rahayu, Mia; Renold, Renold; Ridwan, Masri (Jurnal Ilmiah Poli Bisnis, 2024)
The study found a change in the motivation of visitors to the festival. This study aims to identify visitors' memorable experiences related to tourist attractions at the Dieng Culture Festival, held from 2020 to 2022. The research was conducted using a quantitative-interpretative approach, with research instruments designed to determine visitors' profiles, purposes, and experiences. The sample size consisted of 398 respondents and 5 key informants. The research methodology involved data collection through online surveys and in-depth interviews with key informants. The research findings are presented below. Based on the respondents' characteristics, it can be inferred that most visitors to the Dieng Culture Festival are over 20 years old. The primary purpose of their visit was to experience and participate in the jazz music performances held above the clouds, as indicated by 271 respondents (67.9%). The most prominent attendees are private employees, with 143 respondents (38.5%), followed by students. Notably, 321 respondents (80.5%) learned about the Dieng Culture Festival online. The gender of visitors is dominated by women, with 177 (44.4%) male respondents, while the number of female respondents is 222 (55.6%). Jazz music above the clouds is a memorable programme because it represents visitors' needs. The commodification of the Ruwatan procession of cutting dreadlocks is needed to increase the impression for visitors and strengthen the image of local cultural recognition.